2020
DOI: 10.30564/jpr.v2i3.1932
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Asian Racism in the Shadow of COVID-19 in the USA: Reported Incidents, Psychological Implications, and Coping Resources

Abstract: Racism, which has been a deeply rooted feature of so many human societies across the world for centuries, has become rampant in the shadow of the COVID-19 pandemic. In the past racism was thought to be as somehow “natural” or “biological.”  Later on, sociologists recognized “race” as a socially and culturally constructed ideology, which exists in a society at both the individual and institutional levels. Further down the timeline, psychologists viewed racism as an individual or a collective psychological defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Edara (2020) reported that marginalized populations are often targeted for exclusion and violence during epidemic outbreaks. Edara’s study was both conceptual and included a content analysis of reports of harassment.…”
Section: Resultsmentioning
confidence: 99%
“…Edara (2020) reported that marginalized populations are often targeted for exclusion and violence during epidemic outbreaks. Edara’s study was both conceptual and included a content analysis of reports of harassment.…”
Section: Resultsmentioning
confidence: 99%
“…East and Southeast Asian communities and individuals have been targeted globally with hate speech, including slurs, dehumanization, and slanderous, stereotyping comments about Chinese cuisine (Albader, 2020 ; Hu et al, 2020 ; Tahmasbi et al, 2021 ). Anti-Asian hate-crimes reports also spiked since the beginning of the pandemic in North America (Edara, 2020 ; Gover et al, 2020 ; Kotyk, 2020 ; Tessler et al, 2020 ; Tsai et al, 2020 ), Europe (Gao and Sai, 2020 ; Pellegrino, 2020 ; Velásquez et al, 2020 , preprint) and Australia (Furlong and Finnie, 2020 ). In India, people from northeastern states with more phenotypically East Asian features have been discriminated against and attacked (Haokip, 2020 ).…”
Section: Within-society Intergroup Relationsmentioning
confidence: 99%
“…It is important to keep in mind, given the timeframe, that Covid-19 illuminated many of the cultural embeddings against Asians and Asian-Americans that predate the pandemic. In the United States, there has been a history of hostility directed toward China and Chinese people in the context of epidemic events (Edara, 2020). This creates unique circumstances where anti-Chinese -and, as an extension, anti-Asian -perceptions and behaviors flared up among the public more generally in much less subtle and sometimes violent ways (Edara, 2020).…”
mentioning
confidence: 99%
“…In the United States, there has been a history of hostility directed toward China and Chinese people in the context of epidemic events (Edara, 2020). This creates unique circumstances where anti-Chinese -and, as an extension, anti-Asian -perceptions and behaviors flared up among the public more generally in much less subtle and sometimes violent ways (Edara, 2020). These issues do not exist in a vacuum and racism is deeply ingrained in society, persisting subconsciously even underneath outwardly supportive attitudes (DeAngelis, 2009).…”
mentioning
confidence: 99%